Discourses of motherhood and women's health: Maternal Thinking as feminist politics. (February 2014) - Robinson, Fiona
Using the debate surrounding the Canadian government's 2008 Muskoka Initiative on Maternal, Newborn and Child Health as a central example, this article considers the construction of women and women's health in global health policy. Specifically, it considers the contributions of Sara Ruddick's philosophy to the task of unravelling the ethical and political meanings of 'motherhood', and the relationship between maternal thinking and feminist politics in global social policy. This article argues that while Ruddick's Maternal Thinking has often been read as a normative ethics that asserts the moral authority of mothers' voices and ways of being, it can also be read as a feminist political theory. In particular, Ruddick's work provides feminists with a critical resource for considering the ways that masculinist power can drive a wedge between 'mothers' and 'feminists', thereby obscuring the need for feminism to consider all aspects of mothering as central to their political goals. Far from limiting our understandings of women and their roles in international politics, Ruddick's work provides us with crucial insights into the discursive construction of women in global policy initiatives, as well as offering key starting points for strategies of resistance.